An evaluation of the acceptability of guava halves at various treatment with ascorbic acid (Psidium guajava L.) cv. Peru. - Magalona, Hera U.
Guava ( Psidium guajava L. ) CV. peru halves were thermally processed by water-bath method and evaluated to determine effect of ascorbic acid treatment. Chemical components, sensory attributes and microbiological characteristics were investigated. Results obtained from treated guava halves were compared with untreated control. Over the 4 -week storage period, ascorbic acid treatment did not produce any considerable impact and significant difference on sensory attributes, product preference and chemical components. However, microbiological analysis revealed that the untreated control has more number of colonies expressed as the number of microorganisms per gram of material than the treated one.